Parametric Studies of Economical Expect on Desalination Plant Hardness Removal via Resin - Singh Yadav, Dr. Rajeev (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Presence of high amount of calcium and/or magnesium makes the water hard as these ions in water react with other chemical agents and constituents of metallic plumbing etc. The process accelerates in the presence of heat. It decreases the efficiency of the unit operation due to the formation of scales. Hence, scaling is the main issue for which hard water is required to be treated or polished. De-mineralized water finds wide application in the fields of steam generation plant, high-pressure boiler feed, power- production plant, process plant, cooling systems, steel mills, refineries, petrochemical complexes, hydrometallurgical, metals finishing etc. The high-purity water from a de-mineralized plant is typically used in computer chip, micro-electronics, semiconductor industries. Keywords: hardness removal, poly (acrylamide carboxylic acid) or PAC, scaling, calcium, resin, effluent, parametric studies.